1997
DOI: 10.1149/1.1837985
|View full text |Cite
|
Sign up to set email alerts
|

Process Characteristics for Subatmospheric Chemical Vapor Deposited Borophosphosilicate Glass and Effect of Carrier Gas

Abstract: Borophosphosilicate glass (BPSG) has been widely used as a premetal dielectric to achieve excellent gap fill and planarization due to its reflow capability. In this paper, we present some characterizations of subatmospheric chemically vapor deposited BPSG, aiming at developing a mechanistic understanding of this process. By comparing the effect of controlling variables on the film properties of BPSG and undoped silicon oxide, we conclude that this deposition process is controlled by the gas-phase diffusion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Such dependencies are shown in Fig. 9a for the same SABPSG reactor design using data of Xia et al 12 Results from recalculation of these data into the dependence of the deposition rate on the residence time t are shown in Fig. 9b (t ϭ x/G, where x is the distance between gas injector and the wafer surface while G is the gas velocity under particular deposition conditions).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Such dependencies are shown in Fig. 9a for the same SABPSG reactor design using data of Xia et al 12 Results from recalculation of these data into the dependence of the deposition rate on the residence time t are shown in Fig. 9b (t ϭ x/G, where x is the distance between gas injector and the wafer surface while G is the gas velocity under particular deposition conditions).…”
Section: Discussionmentioning
confidence: 98%
“…9 To date, there has been relatively little information available on the phenomena of TEOS-ozone BPSG deposition at atmospheric and reduced pressure. [9][10][11][12][13] There is no thorough understanding of the mechanism of USG and BPSG film deposition in TEOS-ozone reaction mixture, its excellent gap-filling properties, as well as specific film properties.…”
mentioning
confidence: 99%
“…This made TEOS-ozone CVD process applicable for new generations of IC devices, basically due to urgent gap-filling needs of sub-quarter micron IC technology. A few lowtemperature thermally-activated IC production tools and CVD processes for thin films of silicon dioxide, phosphosilicate and borophosphosilicate glasses were studied and developed in a mid of 1990 th , [15][16][17][18][19][20] see also summary in the author's summary 21 and a monograph. 22 Unique features of TEOS-ozone CVD processes for silicon dioxide (frequently called also "undoped silicate glass", USG) were described in details in.…”
mentioning
confidence: 99%
“…As may be seen, high concentration O 3 flow and concentration, high substrate temperature, and high pressure are necessary to achieve void-free gap fill, low shrinkage, and high etch resistance, whereas deposition rate and film stress can be adjusted by TEOS and H e flow. Because the USG process is controlled by surface reactions, 18 the film deposition rate decreases greatly with increasing surface temperature. The film uniformity is also controlled by the substrate temperature uniformity.…”
mentioning
confidence: 99%
“…As a result of the reaction mechanism, where surface reaction is found to be the rate-determining step, 18 TEOS-O 3 films exhibit surface and pattern sensitivity due to the participation of surface active sites, 19,20 i.e., film properties such as wet etch rate, shrinkage, and step coverage, depend strongly on the substrate structure. In their recent publication, Huang, et al found that such effect can be reduced by decreasing the O 3 -TEOS ratio.…”
mentioning
confidence: 99%